Photoluminescent CaCu3Ti4O12-Based Thin Films Synthesized by a Sol-Gel Method - Parra, Rodrigo [UNESP]; Joanni, Ednan [UNESP]; Espinosa, Jose W. M. [UNESP]; Tararam, Ronald [UNESP]; Cilense, Mario [UNESP]; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Wiley-Blackwell, 2008)
Results on the characterization of photoluminescent CaCu3Ti4O12-based films, prepared from a sol-gel precursor and heat treated at 700 degrees C, are reported for the first time. The samples showed two emission bands at 554 and 800 nm when excited with a 488 nm Ar-ion laser. The photoluminescent emission measured at room temperature in thin films was attributed to complex vacancy clusters. The films consisted of CaCu3Ti4O12 with traces of TiO2, CuO, and CaTiO3 and showed porous structures with an average particle size of 50 nm under atomic force microscopy resolution.